Rekonstruksi Pencegahan Terorisme Berbasis HAM dan Pemberdayaan Masyarakat di Wilayah Pascakonflik Poso - Bambang Afriadi; Rahmat Bakri; Kamal Kamal (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to analyze the protection and fulfillment of human rights in community empowerment-based terrorism prevention in Poso Regency and to evaluate the effectiveness of law enforcement based on Law Number 5 of 2018 and Presidential Regulation Number 7 of 2021. Poso Regency was selected due to its long history as a post-conflict area and its previous role as a base for the East Indonesia Mujahideen group. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that Indonesia’s terrorism prevention framework has accommodated preventive measures, deradicalization, counter-radicalization, and community participation. However, its implementation continues to face several challenges, including gaps between legal norms and practical application, weak inter-institutional coordination, limited resources, and social stigma toward communities affected by conflict and terrorism. Terrorism prevention in Poso should therefore be directed toward an approach that balances security, human rights protection, community empowerment, and the strengthening of local values so that the law is not only formally effective, but also socially accepted and capable of building sustainable social resilience within the community.